2020
DOI: 10.1037/pne0000238
|View full text |Cite
|
Sign up to set email alerts
|

Use of sign language does not favor recognition of static and dynamic emotional faces in deaf people.

Abstract: Facial expressions are especially relevant for deaf people because, in addition to the emotional content, they assume linguistic functions exclusive to sign languages. Objective: We aimed to verify whether the better recognition of facial expressions in deaf people is also maintained for stimuli with greater ecological validity. Method: In the present study, we investigated the recognition of static (photographs) and dynamic (videos) facial expressions in: (a) deaf signers with profound congenital or early acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The content and boundaries of the emotion terms used, however, depend on the culture and language of the community whether that uses speech or sign (Dailey et al, 2010;Russell, 1994). While it has been suggested that deaf signers may categorize facial emotions in ways that differ from the hearing community (Claudino, da Costa, Nascimento & Torro, 2020;Grossman & Kegl, 2007), other studies show that deaf signers do show similar facial expression categorization abilities for both static and dynamic images of the 'universal facial expressions' 3 to those for hearing people who use spoken language (Rodger et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The content and boundaries of the emotion terms used, however, depend on the culture and language of the community whether that uses speech or sign (Dailey et al, 2010;Russell, 1994). While it has been suggested that deaf signers may categorize facial emotions in ways that differ from the hearing community (Claudino, da Costa, Nascimento & Torro, 2020;Grossman & Kegl, 2007), other studies show that deaf signers do show similar facial expression categorization abilities for both static and dynamic images of the 'universal facial expressions' 3 to those for hearing people who use spoken language (Rodger et al, 2021).…”
Section: Introductionmentioning
confidence: 99%